Corporate Social Responsibility: Qualitative and Quantitative Content Analysis Study - Setiawan, Temy; Sugianto, Marshelli; Dahlan, Kandi Safia Senastri; Purwanti, Ari (The Indonesian Accounting Review, 2023)
In the midst of a growing legitimacy gap, CSR disclosure is becoming increasingly important. Comprehensive CSR disclosures, especially in the mining industry sector, are expected to demonstrate accountability and transparency to stakeholders. This study seeks to develop indicators of CSR disclosure that are commonly used by mining sector companies with a cross reference method from various research articles and adapted to the GRI standard. There are 24 main indicators obtained after developing indicators. Furthermore, these indicators are used in content analysis techniques to measure CSR disclosure. The results of this study indicate that companies in the mining industry sector still tend to use quantitative disclosures and disclosures on material aspects that focus on only a few indicators. This research contributes to the development of indicators and mapping of disclosures commonly made by mining sector companies that are listed on the Indonesia Stock Exchange for the period 2017 – 2019.